Quality assessment and biochemical characterization of probiotic Lactobacillus species isolated from yogurts fermented either by Tamarindus indica or Capsicum annuum - Sowmiya Thiagarajan; Emmanuel Bhaskar; Veeraraghavan Gayathri; Parthasarathy Mohanalakshmi; Santhi Silambanan (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2025)
Yogurt is used to treat various digestive ailments. However, there are limited studies of the biochemical and microbiological properties of yogurt. This study aimed to assess the quality and biochemical characteristics of probiotic Lactobacillus species isolated from yogurts fermented with Tamarindus indica or Capsicum annuum. Three yogurt samples were used for analysis; two were homemade, using either Tamarindus indica L. or Capsicum annuum L. to initiate fermentation. Third was a commercial yogurt obtained from the grocery market. A proximate analysis was carried out. To identify microbiological strains, yogurt samples were cultured on nutrient- and De Man-Rogosa-Sharpe agars. Biochemical characteristics were examined, and probiotic species were identified through 16S rRNA analysis. The results showed that traditional yogurts had lower energy content due to reduced carbohydrate and fat levels while exhibiting higher protein content. Escherichia coli and coliforms were detected in the commercial yogurt, whereas traditional yogurts were free from these harmful bacteria, highlighting their potential safety. The biochemical characteristics of all yogurt samples were largely similar. C. annuum L. demonstrated a positive oxidase test, indicating the presence of an electron transport chain in the Lactobacillus species found in the yogurt fermented with C. annuum L. Microbial analysis revealed that L. acidophilus was predominant in traditional yogurt, while commercial yogurt contained L. plantarum. These findings suggest that homemade yogurts, with their higher protein content, lower fat and carbohydrate levels, and absence of harmful bacteria, offer a safer and potentially more beneficial probiotic alternative to commercial yogurt. The specific Lactobacillus strains present in traditional yogurts may contribute to their antimicrobial properties, supporting their probiotic potential.